Differential Effects of Antiretroviral Nucleoside Analogs on Mitochondrial Function in HepG2 Cells - Pan-Zhou, Xin-Ru (American Society for Microbiology, 2000)
Numerous studies have reported effects of antiviral nucleoside analogs on mitochondrial function, but they have not correlated well with the observed toxic side effects. By comparing the effects of the five Food and Drug Administration-approved anti-human immunodeficiency virus nucleoside analogs, zidovudine (3′-azido-3′-deoxythymidine) (AZT), 2′,3′-dideoxycytidine (ddC), 2′,3′-dideoxyinosine (ddI), 2′,3′-didehydro-2′,3′-deoxythymidine (d4T), and β-L-2′,3′-dideoxy-3′-thiacytidine (3TC), as well as the metabolite of AZT, 3′-amino-3′-deoxythymidine (AMT), on mitochondrial function in a human hepatoma cell line, this issue has been reexamined. Evidence for a number of mitochondrial defects with AZT, ddC, and ddI was found, but only AZT induced a marked rise in lactic acid levels. Only in mitochondria isolated from AZT (50 μM)-treated cells was significant inhibition of cytochrome c oxidase and citrate synthase found. Our investigations also demonstrated that AZT, d4T, and 3TC did not affect the synthesis of the 11 polypeptides encoded by mitochondrial DNA, while ddC caused 70% reduction of total polypeptide content and ddI reduced by 43% the total content of 8 polypeptides (including NADH dehydrogenase subunits 1, 2, 4, and 5, cytochrome c oxidase subunits I to III, and cytochrome b). We hypothesize that in hepatocytes the reserve capacity for mitochondrial respiration is such that inhibition of respiratory enzymes is unlikely to become critical. In contrast, the combined inhibition of the citric acid cycle and electron transport greatly enhances the dependence of the cell on glycolysis and may explain why apparent mitochondrial dysfunction is more prevalent with AZT treatment.